Alberta’s 2002 Teacher Strike: The Political Economy of Labor Relations in Education - Barnetson, Bob (Education Policy Analysis Archives, 2010)
In 2002, approximately two thirds of school teachers in the Canadian province of Alberta went on strike. Drawing on media, government and union documents, this case study reveals some contours of the political economy of labor relations in education that are normally hidden from view. Among these features are that the state can react to worker resistance by legally pressuring trade unions and justifying this action as in the public interest. This justification seeks to divide the working class and pit segments of it against each other. The state may also seek to limit discussion and settlements to monetary matters to avoid constraining its ability to manage the workplace or the educational system. This analysis provides a basis for developing a broader theory of the political economy of labor relations in education. It also provides trade unionists in education with information useful in formulating a strike strategy.